THE EFFECT OF ROA, EPS, PER ON STOCK RETURN OF FOOD AND BEVARAGE COMPANIES - Sany Hermin Rotua Sitorus; Ardina Pandiangan; Emeldasari Sinaga; Renni Romauli Manurung; Ferdinand Napitupulu (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study has aim to determine the effect of accounting profit, cash flow operating activity, cash flow of investment activities, cash flow funding activities on stock prices in the consumer goods industry company registered in (IDX). The sub-sector selected as a data study is the food and beverage sub-sector in 2018-2020, by having a population of 52 companies and using a purposive sampling technique of 27 companies and years of observation of this study are 3 (three) years and data obtained from www .idx.co.id. The data method used is multiple linear analysis. The approach carried out in this study was a quantitative and descriptive approach, based on the results of this researcher that accounting profit, cash flow operating activity, cash flow investment activity, cash flow funding activities had a significant effect on stock prices. The results of the simultaneous hypothesis gained that accounting profit, cash flow operating activity, cash flow investment activity, cash flow funding activities, had a significant effect on stock prices.